Pengaruh Current Ratio, Debt To Equity Ratio, Dan Return Of Equity Terhadap Return Saham Dengan Pemediasi Harga Saham (Studi Pada Perusahaan Pertambangan Batu Bara Yang Melaksanakan Corparate Social Responsbility) - Ningsih, Ayu Agus Tya; Arifin, Rosyid; Poernomo Poetra, Moh. Hardisty Novan Adiwena (Manajemen & Bisnis Jurnal, 2025)
This study aims to analyze the effect of the current ratio, debt-to-equity ratio, and return on equity on stock returns, with stock price as a mediator in coal mining companies implementing Corporate Social Responsibility. This study is based on increasing coal production and profits from several coal companies in Indonesia. This study uses a quantitative approach with secondary data obtained from company financial reports. The sample size was 16 coal companies listed on the Indonesia Stock Exchange. The results show that the current ratio has no significant effect on stock returns and stock prices. While the debt-to-equity ratio has a significant effect on stock returns but no effect on stock prices. Return on equity has no significant effect on stock returns but does have a significant effect on stock prices. Stock prices do not significantly influence stock returns and do not mediate the relationship between the current ratio, debt-to-equity ratio, or return on equity on stock returns. This research can serve as a reference for investors in making investment decisions and serve as a reference for other similar research.